Australian overseas trained psychiatrists' perspective of up‐skilling programme. Issue 2 (2014) - Pam McGrath; Saras Henderson; Sidney Cabral; David Crompton
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to report research findings on the perspectives of overseas trained psychiatrists (OTPs) on the "The Overseas Trained Specialist Up‐Skilling Programme" (OTSUP), initiated in Queensland, Australia to assist OTP's to prepare for the Royal Australian and New Zealand College of Psychiatrist (RANZCP) Fellowship examination. Ascertaining and utilisation of OTP's views about the programme will enable improvements to be made to the programme and better implementation. Design/methodology/approach – An exploratory qualitative design was utilised for the study in order to provide insights on the quality and effectiveness of the OTSUP. Findings – Centred around two main themes. The first theme included participant's knowledge about the up‐skilling programme with its subthemes of "finding out about the programme"; "perceived aims of the programme"; and "educational events supporting the programme". The second theme revolved around participants' perceived benefits of the up‐skilling programme with its four subthemes such as, first, individualised support, second, the opportunity to improve practical and communication skills through OTSUP educational events, third, access to peer support and fourth, provision of specific information on the RANZCP examination process. Research limitations/implications – Limitations as this was a qualitative study, the findings can only be applicable to a similar context. Nevertheless, the findings do provide support for an educational initiative that assisted the OTS to better prepare for the RANZCP examination. To gain further insight into challenges faced by OTS with successfully passing the examination in less frequent attempts, programmes such as the OTSUP need to be improved and sustained. Originality/value – The findings provide valuable insight into how OTPs view the up‐skilling programme. Moreover, the findings pave the way forward in how the programme can be improved in the future to assist OTPs prepare for the RANZCP examination. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors would like to thank all the participants who willing gave their time in agreeing to be interviewed and the Griffith University research team that collected and analysed the data. Thanks also to Ms Nicole Rawson for her work in coding and participating in the analysis. One of the authors Dr Sidney Cabral was psychiatrist with the programme but the data collection and analysis was conducted independently by researchers from Griffith University. Interviews, data collection and analysis were done by independent researchers and other aspects of the article were discussed as a group with the team of authors. </ack>